Variability of fluvial sediment supply to the Laptev Sea continental margin during Late Weichselian to Holocene times: Implications from clay-mineral records. - Müller, Claudia; Stein, Ruediger (PANGAEA, 2000)
Three sediment cores from the Laptev Sea continental margin were investigated for their clay mineralogy by X-ray diffraction to study the fluvial sediment supply since the late Weichselian. In the study area, the clay-mineral composition of surface sediments is characterized by distinct regional variations. The source area for smectite in the eastern Eurasian Basin is the Putoran Plateau drained by the Khatanga and Yenisei rivers. Currents caused by river discharge and the inflow of Atlantic water masses along the Eurasian continental margin are responsible for sediment distribution. In the sediment cores, smectite and illite contents show an opposite trend which mainly results from variable smectite supply. During MIS 2 the amount of smectite on the Laptev Sea continental margin never exceeds 10 rel.%. Probably, reduced river discharge and the lowered sea level during MIS 2 caused a decreased sediment supply to the Laptev Sea. Additionally, the Putoran Plateau was covered by an ice sheet during the Late Weichselian preventing the erosion of smectite-rich soils. In contrast, maximum smectite contents (up to 30 rel.%) in Holocene sediments result from increased sediment input by the Khatanga River and from the Kara Sea through the Vilkitsky Strait and via St. Anna Trough into the western Laptev Sea.
Sedimentology of three cores from the Laptev Sea continental margin (Arctic Ocean)
Keywords: Arctic Ocean; ARK-IX/4; ARK-XI/1; AWI_Paleo; KAL; Kasten corer; Laptev Sea; Paleoenvironmental Reconstructions from Marine Sediments @ AWI; Polarstern; PS2458-4; PS27; PS27/038; PS2741-1; PS2767-4; PS36; PS36/028; PS36/066; Quaternary Environment of the Eurasian North; QUEEN